Study on rationality of different fixed dose drug combinations in tertiary care hospital: an evaluation study - Rajitha, Maddala; Shaik, Altaf Hussain; Simpson, G. B.; Shanthi, A. Vishwa (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The fixed dose drug combinations (FDCs) of drugs is defined as product of two or more active ingredients in a defined composition. There is a need to study the pattern of prescription from time to time to evaluate their rationality. In this context we undertook this study to know the prescription pattern of FDC in our setting. To study the rationality of different prescribed FDCs. Methods: This is a prospective study which is carried out in NIMRA Institute of medical sciences which is a tertiary care teaching private hospital. For this study we have collected one thousand prescriptions of patients for 3 months that is from 10th March 2017 to 25th of June 2017 including both in-patients as well as outpatients. Selection criteria of patients mainly basing on their willingness to give prescriptions. Institutional ethical committee permission was taken for the study. The prescribed FDCs were compared with the essential drug list of FDCs approved by Drugs Controller General of India, July 2018. we have used descriptive statistics to analyze data. The percentage of FDCs used in each class and their contribution to overall FDCs were calculated. Results: In a total of 2952 drugs were prescribed, of this 747 were FDCs and 2205 were non FDCs. In the prescribed FDCs 89.2% drugs were rational and 10.8% drugs were irrational. Conclusions: From this study, we can conclude that 10.8% of irrational prescription of fixed dose drug combinations are prescribed in Nimra Institute of Medical Sciences which is a tertiary care teaching private hospital.